How Financial Development Affects Carbon Dioxide Emissions In Indonesia? A Cointegration And Causality Analysis - Pradana, Erlangga Gilang; Solikin, Akhmad (SEAN Institute, 2024)
Reducing carbon dioxide emissions is key to mitigating the adverse effects of global climate change. The expansion of the financial industry has become a vital aspect of economic growth, yet it may induce carbon dioxide emissions. This study investigates the relationship and causality between financial development and carbon dioxide emissions in Indonesia. The analysis uses data from 1971 to 2018 for per capita carbon dioxide emissions and credit provided by the financial sector as the main variables, while uses GDP, energy consumption, export value, and population density as the control variables. The Johansen cointegration test and VECM Granger causality are used to analyze the relationship and causality between main variables. The result indicates that financial development has a positive short-run and long-run relationship with carbon dioxide emissions, with bidirectional causation in the long run. It suggests that the government's program to develop the financial sector may harm Indonesia's carbon dioxide emissions. Therefore, the government should consider the environmental implications of financial development and introduce policies that incentivize financial actors to promote green finance and low-carbon technologies and support green initiatives.